Spazi e relazioni di cura per le donne richiedenti asilo - Bochi, Valeria (Antropologia Pubblica, 2024)
In a context of second non-emergency hospitality, the article analyzes the interaction between social workers, medical staff and asylum seekers women, considering their sexual and reproductive health and the asymmetrical relationships among them. Reproduction is an interesting prism to analyze not only the dynamics of power/subjection in the construction of women subjectivity "in transit", but also to highlight the interaction between the staff involved in this relationship. This constitutes the physical and symbolic space where the vulnerability of women and their children is actively built. During this interaction pregnancy, motherhood, contraception, abortion become dimensions lived and acted differently and where this difference can lead to opposition, resistance, discrimination or violence, especially when real or presumed attempts to shape women's sexual and reproductive customs to European standards are determined.